Sulfated fucoidan FP08S2 inhibits lung cancer cell growth in vivo by disrupting angiogenesis via targeting VEGFR2/VEGF and blocking VEGFR2/Erk/VEGF signaling. Issue 1 (1st November 2016) - Chen, Huanjun; Cong, Qifei; Du, Zhenyun; Liao, Wenfeng; Zhang, Lei; Yao, Yanli; Ding, Kan
Highlights: FP08S2, a sulfated fucoidan, inhibited the tube formation, migration and invasion of HMEC-1 cells in vitro . This polysaccharide interfered with the interaction of VEGF with VEGFR2 to exert anti-angiogenetic effect. VEGFR2/Erk/VEGF signaling pathway was blocked by FP08S2 in HMEC-1 cells. Furthermore, FP08S2 suppressed angiogenesis and tumor growth in vivo in A549 lung cancer xenograft model. This study indicated that FP08S2 could be an anti-angiogenic candidate agent for lung cancer therapy. Abstract: Fucoidan may inhibit angiogenesis. However, its functional target molecule and the underlying mechanism are still vague. In the present study, we showed that sulfated fucoidan FP08S2 from Sargassum fusiforme inhibited tube formation as well as migration and invasion of human microvascular endothelial cells (HMEC-1). In addition, FP08S2 was confirmed to disrupt VEGF-induced angiogenesis both in vitro and in vivo . Further study indicated that FP08S2 could bind to both VEGF and VEGFR2 to interfere with VEGF–VEGFR2 interaction. Moreover, VEGFR2/Erk/VEGF signaling pathway was blocked by FP08S2 in HMEC-1 cells. Importantly, FP08S2 impeded the growth and microvessel formation of A549 cancer cell xenograft in nude mice. These results suggested that FP08S2 presented remarkable anti-angiogenic activity via blocking VEGF signaling and could be a potential novel leading compound to inhibit lung cancer cell growth.